Comparison of prognostic values of high-sensitivity cardiac troponin T and N-terminal prohormone brain natriuretic peptide to assess mortality in elderly inpatients - Chen JR (Dove Medical Press, 2018)
Jie-Ruo Chen,1 Qing Wang,1 Wei Wu,2 Shao-Jing Zhang1 1Department of Geriatrics, Fuxing Hospital, affiliated to Capital Medical University, Beijing, China; 2General Practice Ward, Fuxing Hospital, affiliated to Capital Medical University, Beijing, China Background: Studies have shown that increases in low-level high-sensitivity cardiac troponin T (hs-cTnT) and N-terminal prohormone brain natriuretic peptide (NT-proBNP) in the elderly population lead to high risk of adverse clinical outcomes, such as mortality. In this study, associations between the two biomarkers and long-term mortality in elderly patients hospitalized for medical conditions other than acute cardiovascular events were investigated. A comparison of the predictive value of hs-cTnT and NT-proBNP for all-cause mortality was conducted. Methods: A cohort of 715 elderly inpatients free of acute cardiovascular events was initially recruited. Based on tertiles of baseline hs-cTnT and NT-proBNP levels, the elderly were arranged into low, middle, and high groups. The mortality of each group was observed and the predictive values of hs-cTnT and NT-proBNP compared. Additionally, all-cause mortality was analyzed for hs-cTnT and NT-proBNP combined. Results: There were 135 (18.9%) all-cause mortality cases identified during follow-up (median 47 months). The upper tertile of hs-cTnT was significantly associated with an increased risk of mortality (HR 3.29, 95% CI 1.85–5.85), even after adjustment for potential confounders. However, there were no significant differences observed in mortality rates among the three NT-proBNP groups after adjustment for potential confounders (HR 1.77, 95% CI 0.83–3.17). Compared to NT-proBNP, hs-cTnT was a better predictor of mortality, as area under curves for hs-cTnT and NT-proBNP at 60 months were 0.712 (95% CI 0.616–0.809) and 0.585 (95% CI 0.483–0.6871), respectively. Also, the combination of the two cardiac biomarkers did not render a better predictive value for mortality than hs-cTnT alone. Conclusion: Unlike hs-cTnT, baseline NT-proBNP levels failed to show an independent association with all-cause mortality in hospitalized elderly without acute cardiovascular events. hs-cTnT provided significant prognostic value for mortality in the study cohort. Keywords: high-sensitivity cardiac troponin T (hs-cTnT), N-terminal prohormone brain natriuretic peptide (NT-proBNP), nonacute cardiovascular events, elderly patients